Governance, Laws, and Water Interventions in the Yellow River Basin Over the Past 60 Years: From Supply- to Demand- Side Management - Xue, Yunpeng; Sun, Yan; Ringler, Claudia (International Food Policy Research Institute, 2010)
For thousands of years, the Yellow River Basin (YRB) has been the cultural and economic center of China. The nutrient-rich soils transported by the river from the Loess Plateau have supported an economy largely based on agriculture-and increasingly irrigated agriculture. Since the 1978 reforms, industries began to develop in the lower river reaches; since then, industries have gradually expanded westward toward relatively cheaper labor and more abundant raw materials. Today the basin is home to important mining, chemical, and manufacturing industries as well as several urban areas housing millions of people.